The truth about thriving gig workers: Why job demands and coping mechanisms are not enough? - Wendra, Wendra; Siregar, Diyah Dumasari; Abd Samad, Khairunnisa (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2024)
Gig workers often face challenging work environments characterized by uncertain and unpredictable incomes, limited project opportunities, and unclear career paths. Despite these challenges, some gig workers succeed in moving from merely surviving to thriving in their work. While existing studies explore their struggles and resilience, the process that enables this transformation still needs to be explored, particularly in the context of Indonesia’s rapidly growing digital creative industry. Addressing this gap, this study aims to develop a model for thriving at work among gig workers in Indonesia’s digital creative industry. Using a quantitative approach, questionnaires were purposively distributed to 333 gig workers. Data analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM) revealed several key findings. Job demands directly influenced coping strategies, and psychological capital directly impacted goal setting. Both psychological capital and goal setting significantly influenced thriving at work, with goal setting mediating the relationship between psychological capital and thriving. However, job demands and coping strategies had no significant impact on thriving at work, nor did coping strategies mediate the relationship between job demands and thriving. These findings highlight that thriving in the gig economy relies more on internal resources like psychological capital and goal-setting skills, rather than external pressures such as job demands or coping mechanisms, emphasizing the need for personal development.